CONCEPTIONS ASSOCIATED WITH THE CULT OF NATURE IN THE BELIEF SYSTEMS OF THE UZBEK PEOPLE - Ilhom Sultonovich Bobokhojayev (Western European Studies, 2024)
The Uzbek people are among the peoples with a complex ethnic structure. They have practiced various customs and rituals for many years due to the integration of the cultures of the Turkic peoples, which was formed as a result of the interaction of historical processes. The article highlights the views of the Uzbek people regarding cults in their religious beliefs.
Keywords: Plant-like; zoomorphic; Sayrab plane tree